Pemasaran Produk Nasi Goreng: Strategi Menuju Keberhasilan Analisis Metode IFAS-EFAS - Lestari Sayudi; Afrina Sari (Yayasan Literasi Sains Indonesia, 2026)
This study aims to examine the relationship between culinary businesses, particularly fried rice businesses, and the use of SWOT analysis as a strategic tool in business development. The study applies Strategic Management Theory because strategic management is closely related to the use of SWOT analysis in identifying strengths, weaknesses, opportunities, and threats that influence a business. Through this approach, business actors can better understand internal and external factors that affect the sustainability and competitiveness of their culinary businesses. The methodology used in this research is a qualitative method with a phenomenological approach. Phenomenological qualitative research is commonly used in social studies to understand and explore the meaning of a phenomenon experienced by individuals or groups. This approach aims to reveal shared meanings derived from the life experiences of individuals related to a particular concept or phenomenon, in this case the fried rice culinary business. Based on the analysis results, the difference in the internal factor score is 0.95 and the external factor score is 0.63. These findings indicate that the fried rice business still has good opportunities to grow and compete in the culinary market despite competition from other culinary businesses such as satay and other traditional foods.